2019
DOI: 10.22270/jddt.v9i4-a.3438
|View full text |Cite
|
Sign up to set email alerts
|

The Antidiabetic and Antioxidant Activity of Coccinea Grandis Voigt Stem Extract in Streptozotocin Induced Diabetic Rats

Abstract: Objective: In the present study, the antidiabetic and antioxidant study of stem part of Coccinea grandis Voigt plant extracts in Streptozotocin induced diabetic rats were investigated. Materials and methods: Fifty four Wistar albino rats were used with nine groups and with six rats in each group. 45 mg/kg body weight streptozotocin was administered to group 2 to 9. Group 2 was diabetic control. Group 3 was given with glimepiride as standard drug. Group 4 and 5 were given petroleum ether extract 250 and 500 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
1
0
1
Order By: Relevance
“…Em outros estudos (Kim & Kim 2012;Ahangarpour et al 2017;Momin & Yeligar 2019), que também empregaram plantas medicinais como tratamentos, os autores observaram redução nos níveis de triglicerídeos. Esses estudos sugerem que a atividade antioxidante dos extratos pode ser responsável pelos resultados encontrados.…”
Section: Resultsunclassified
“…Em outros estudos (Kim & Kim 2012;Ahangarpour et al 2017;Momin & Yeligar 2019), que também empregaram plantas medicinais como tratamentos, os autores observaram redução nos níveis de triglicerídeos. Esses estudos sugerem que a atividade antioxidante dos extratos pode ser responsável pelos resultados encontrados.…”
Section: Resultsunclassified
“…This is in line with Nurhaliza's research (in Munira et al, 2020) who added that the largest class of compounds found in Chinese betel nut are flavonoids. According to Angelina et (in Momin & Yeligar, 2019), the Chinese betel plant (Peperomia pellucida L.) contains alkaloids, flavonoids, saponins, tannins and triterpenoids (Slavova & Karanasios, 2018). Apart from these ingredients, Chinese betel (Peperomia pellucida L.) also contains other chemical compounds that have been studied previously, namely essential oil compounds, especially carotol dillapiole , βcarophyllene (Patra et al, 2020).…”
Section: Chinese Betel Nut (Peperomia Pellucida L) Phytochemicalsmentioning
confidence: 99%